Coimplanted Endothelial Cells Improve Adipose Tissue Grafts' Survival by Increasing Vascularization. Issue 2 (March 2015) - Luo, Xuan; Cao, Weigang; Xu, Haisong; Wang, Lin; Zhang, Zhiliang; Lu, Yi; Jin, Xin; Ren, Xiaoyun; He, Jiyin; Fu, Mingang; Huang, Yixiong; Pi, Qingmeng; et al.
<x xml:space="preserve">Abstract</x> Background With goal of improving fat graft survival, many studies have focused on supplementing cells in the graft fat. In these studies, enhanced vascularization is considered the most important mechanism for the improved graft survival. Endothelial cells (ECs) are essential in vessel formation of the vascularization. Therefore, in this study, we coimplanted ECs with adipose tissue to investigate whether the ECs can enhance graft survival in a cell concentration-dependent manner. Methods Endothelial cells were isolated from stromal vascular fraction derived from human liposuction aspirates, and the EC characteristics were confirmed by CD31 immunofluorescence staining, measuring acetylated low-density lipoprotein uptake, and observing the formation of capillary-like tubular structures in Matrigel. During the animal experiment, the isolated ECs were labeled, then added to 0.5-mL fat grafts at different numbers (0.5 × 106, 1 × 106, 2 × 106, and 4 × 106 cells) before subcutaneous implantation in nude mice. Grafts were harvested at 1 week, 1 month, and 2 months after -transplantation, and graft survival and vascularization were evaluated based on weight measurements, histological assessment, and vascular gene expression. Results Stromal vascular fraction–derived vascular cells exhibited typical EC characteristics. The observed differences in explanted graft weight, vessel density, vascular gene expression, and cell tracking result indicated that coimplantation with ECs accelerated vascularization that increased graft survival in a concentration-dependent manner. Over the experimental period, fat grafts implanted with 4 × 106 ECs showed no weight loss and the greatest increases in measures of vascularization. Conclusions Endothelial cells can effectively enhance vascularization in fat grafts, and higher EC concentrations (eg, 4 × 106 ECs/0.5 mL adipose tissue) may best support graft survival.